2017
DOI: 10.1186/s12906-017-2031-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pharmacological education on perceptions, attitudes and use of dietary supplements by medical students

Abstract: AbstractsBackgroundThe ready availability and use of dietary supplements (DS) by the public means that healthcare professionals require education in this area. In the Republic of Serbia, education related to use of DS is included in undergraduate medical training and it is therefore important to assess the effectiveness of this education. The aim of our survey was to investigate the influence of pharmacological education on the use, attitudes and perceptions of risks associated with DS among medical students.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 42 publications
4
31
1
Order By: Relevance
“…Medical sciences students (33.1%) were slightly higher users of dietary supplements than were nonmedical sciences students (28.8%), which is in accordance to similar studies [ 19 , 26 ]. In line with other studies of dietary supplements, for our students, the most popular dietary supplements were vitamins (13.8%) [ 9 , 10 , 18 ]. In addition, many similar studies reported multivitamins and multivitamin-mineral combinations as the most frequently used dietary supplements in the student’ population [ 24 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Medical sciences students (33.1%) were slightly higher users of dietary supplements than were nonmedical sciences students (28.8%), which is in accordance to similar studies [ 19 , 26 ]. In line with other studies of dietary supplements, for our students, the most popular dietary supplements were vitamins (13.8%) [ 9 , 10 , 18 ]. In addition, many similar studies reported multivitamins and multivitamin-mineral combinations as the most frequently used dietary supplements in the student’ population [ 24 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…After joining the EU, Croatia developed regulations on dietary supplements in line with the EU Directive [ 6 ]. The German National Nutrition Survey II showed that 21% of young people used dietary supplements [ 7 ], including 66% of American students [ 8 ], 68% of Serbian students [ 9 ], and 43% of Malaysians students [ 10 ], while in Croatia, there are no existing data about dietary supplements use among young people. Young people are particularly vulnerable to the effects of poor nutrition, including nutrient deficiencies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, medical students in their future clinical practice can have positive impacts on patients health beliefs and supplement use, as well as on those of the general public [ 43 ]. Therefore, some studies also researched the dietary supplements use in health science students to find the difference, especially about their attitudes and knowledge [ 17 , 19 , 24 , 44 , 45 ]. One study conducted in the United States found that the prevalence of dietary supplements use in the students was 66.0% [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, the prevalence of using these supplements among students ranges between 11% and 68% and it is reported that the majority of students use these supplements to be healthy. [7][8][9][10][11][12][13] In the literature, it is also reported that the use of dietary supplements is high in people with the symptoms of orthorexia nervosa (ON), followed by people with healthy eating and normal eating habits, respectively, that the rate of dietary supplement use for overall health is higher in people with healthy eating habits and ON symptoms than in people with normal eating habits and that the rate of dietary supplement use to increase energy, skin, hair, or nail health, digestive or urinary health, to improve mood, bone, joint, or muscle health and to enhance focus/concentration is higher in people with ON symptoms than in people with normal or healthy eating habits. 14 Healthy orthorexia is defined as "healthy interest in diet, healthy behavior with regard to diet, and eating healthily as part of one's identity."…”
Section: Introductionmentioning
confidence: 99%